2011
DOI: 10.1186/1471-2296-12-140
|View full text |Cite
|
Sign up to set email alerts
|

Obesity management and continuing medical education in primary care: results of a Swiss survey

Abstract: BackgroundThe worldwide increase in obesity is becoming a major health concern. General practitioners (GPs) play a central role in managing obesity. We aimed to examine Swiss GPs self-reported practice in diagnosis and treatment of obesity with a special focus on the performance of waist measurement.MethodsA structured self-reported questionnaire was mailed to 323 GPs recruited from four urban physician networks in Switzerland. Measures included professional experience, type of practice, obesity-related contin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 28 publications
2
9
0
4
Order By: Relevance
“…43 Unfortunately, roughly half of primary care physicians seldom or never measure WC. 44,45 Furthermore, errors in measurement and inconsistency of technique are common. 46,47 The NIH/NHLBI cut points that distinguish between people at higher and lower cardiovascular risk are >102 cm (40") for men and >88 cm (35") for women.…”
Section: Waist Circumferencementioning
confidence: 99%
“…43 Unfortunately, roughly half of primary care physicians seldom or never measure WC. 44,45 Furthermore, errors in measurement and inconsistency of technique are common. 46,47 The NIH/NHLBI cut points that distinguish between people at higher and lower cardiovascular risk are >102 cm (40") for men and >88 cm (35") for women.…”
Section: Waist Circumferencementioning
confidence: 99%
“…Good GP knowledge and counselling skills are essential for effective consultation. Providing sufficient training in medical schools and in continuous medical education on how to discuss nutrition and physical activity for weight management and developing the practical tools to support counselling in primary health care may help to increase the frequency of giving advice [8, 32].…”
Section: Discussionmentioning
confidence: 99%
“…Although most health professionals hold favorable attitudes concerning their role in the prevention and treatment of obesity, many have expressed a lack of confidence in their ability to manage obese patients, and their actual professional weight management practices fall below the recommendations set out in the evidence-based guidelines of several countries, for example, health professionals should use every opportunity to help patients with changes to their lifestyles (dietary advice and exercise) [ 2 - 4 ]. This is evident from studies of patients [ 5 - 7 ], physicians [ 8 - 12 ] and nurses [ 13 , 14 ]. Patient surveys have suggested that less than a half of obese patients were advised by their physicians to lose weight [ 5 - 7 ] with a minority of physicians reporting confidence in helping obese patients lose weight [ 8 ], half performing waist measurement [ 12 ], and less than half always providing specific guidance on diet, physical activity or weight control for their adult patients [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is evident from studies of patients [ 5 - 7 ], physicians [ 8 - 12 ] and nurses [ 13 , 14 ]. Patient surveys have suggested that less than a half of obese patients were advised by their physicians to lose weight [ 5 - 7 ] with a minority of physicians reporting confidence in helping obese patients lose weight [ 8 ], half performing waist measurement [ 12 ], and less than half always providing specific guidance on diet, physical activity or weight control for their adult patients [ 11 ]. These findings are consistent with those for nurses with few routinely using the body mass index (BMI) to make clinical judgments of weight status or obesity [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%